Ellagic acid: a review on its natural sources, chemical stability, and therapeutic potential - Sharifi-Rad, Javad; Quispe, Cristina; Castillo, Carla Marina Salgado; Caroca, Rodrigo; Lazo-Vélez, Marco A.; Antonyak, Halyna; Polishchuk, Alexandr; Lysiuk, Roman; Oliinyk, Petro; De Masi, Luigi; Bontempo, Paola; Martorell, Miquel; et al. (Oxidative medicine and cellular longevity, 2022)
Ellagic acid (EA) is a bioactive polyphenolic compound naturally occurring as secondary metabolite in many plant taxa. EA content is considerable in pomegranate (Punica granatum L.) and in wood and bark of some tree species. Structurally, EA is a dilactone of hexahydroxydiphenic acid (HHDP), a dimeric gallic acid derivative, produced mainly by hydrolysis of ellagitannins, a widely distributed group of secondary metabolites. EA is attracting attention due to its antioxidant, anti-inflammatory, antimutagenic, and antiproliferative properties. EA displayed pharmacological effects in various in vitro and in vivo model systems. Furthermore, EA has also been well documented for its antiallergic, antiatherosclerotic, cardioprotective, hepatoprotective, nephroprotective, and neuroprotective properties. This review reports on the health-promoting effects of EA, along with possible mechanisms of its action in maintaining the health status, by summarizing the literature related to the therapeutic potential of this polyphenolic in the treatment of several human diseases.